Marapu Death Prayer as a Locus Theologicus: A Hermeneutical Reading in the Perspective of Inculturated Theology - Si, Stefanus; Martasudjita, E.P.D.; Gozaga, Januario (Litbang STFT Widya Sasana Malang, 2026)
This study is grounded in the phenomenon of double religious belonging among Catholic communities in Sumba who continue to perform the Marapu death prayer, a practice often perceived as potentially generating theological tension. The aim of this research is to examine the theological meaning of the Marapu death prayer and to situate it within the framework of inculturated theology. The study employs a qualitative approach with an ethnographic theological design, using interviews, participant observation, and thematic analysis, which are then interpreted through a Translation Model based on the principle of double fidelity. The findings indicate that the Marapu death prayer embodies five principal meanings: death as a cosmic transition, sacrifice as a mediation of divine relationship, ancestral relation as a transgenerational community, cosmic harmony, and awareness of divine hiddenness. These findings affirm that the practice does not represent a conflict of faith, but rather a religious expression that opens an analogical space for theological dialogue. Consequently, the Marapu death prayer may be understood as a locus theologicus that enriches contextual theology and encourages a more dialogical, contextual, and non-reductionist pastoral approach within the Church.